MEDIA PENDATAAN SATWA LIAR BERBASIS WEB DAN MOBILE - Putra, Farozi Rizky; Sancoko, Sulistyo Dwi (Jurnal Informatika Teknologi dan Sains (Jinteks), 2024)
Indonesia, with its high biodiversity, faces significant challenges in conserving wildlife threatened by climate change, habitat destruction and illegal trade. This research aims to develop a web and mobile-based "Lestari" application, to support wildlife data collection. This application was built using Node.js for the backend, Dart Flutter for the mobile application, and MySQL as the database. Tests show this application increases the efficiency of animal data collection with an intuitive interface that makes it easy for users to enter information such as habitat and number of animals. The high reliability and scalability of Node.js ensures applications can handle multiple requests simultaneously, while Flutter enables a consistent user experience across devices. MySQL is used for effective data management, ensuring data integrity and ease of management. This application supports conservation efforts by providing structured data that facilitates in-depth analysis by researchers, as well as encouraging active public participation in animal reporting, increasing awareness and involvement in environmental conservation. The conclusion of this research shows that the "Lestari" application has succeeded in fulfilling its main objective, namely increasing the efficiency and effectiveness of wildlife data collection. Based on the results of blackbox testing, it shows that web-based and mobile applications are as expected